Canon 1673: Identifying the Competent Ecclesiological Court - Beal, John P. (Roman Replies and CLSA Advisory Opinions 2013, 2013)
Can the judicial vicar of the place where the respondent has a domicile or quasi-domicile delegate the moderator of the tribunal chancery to give consent, after having heard the respondent, to the claim of competence of the tribunal of the domicile of the petitioner in a maariage nullity case?